Inverse Sideways Perspective on a Road: A Drawing by a Blind Adult. (July 2020) - Carboni, Selene; Kennedy, John M.
An unusual drawing of a road has two lines converging sideways, from right to left. The left side of the picture is explicitly described as the location of the observer. Also, the fronts of the cars on the road face left, with the largest car on the right. This sideways perspective is novel. In linear perspective, roads running parallel with the picture surface should be drawn with parallel lines. Lines for roads running orthogonal to the picture surface should converge with elevation. The rule for roads is if converging, then upward, and if sideways, then not converging. The sketch is by a blind woman with modest experience in drawing, including perspective. It suggests an intermediate stage of drawing development, with inconsistent use of the observer's vantage point, in keeping with theories of perspective drawing by the blind and sighted of Willats, Kennedy and others.